Ourika - Duras, Claire de Durfort, duchesse de, 1777-1828 (Salt Lake City, UT : Project Gutenberg, 2015)
"Ourika" by Claire de Duras is a novel published in 1823. A young enslaved girl is rescued from the slave trade and raised in aristocratic Parisian society. Educated and cultured, she lives unaware of racial barriers until a devastating conversation forces her to confront how the world sees her. As she falls in love with someone beyond her reach, she must navigate a society that cannot see past her skin color. This groundbreaking work depicts the first complex black woman narrator in French literature. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Ourika
Release date is 2015-06-29
Produced by Dagny and Marc D'Hooghe (Images made available by the Google Books Project)
Keywords: France -- Fiction; Race relations -- Fiction; Women, Black -- Fiction; Africans -- France -- Fiction